2006
DOI: 10.1097/00042752-200603000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Intratester and Intertester Reliability of Clinical Measures of Lower Extremity Anatomic Characteristics: Implications for Multicenter Studies

Abstract: Abstract:Objective: To determine whether multiple examiners could be trained to measure lower extremity anatomic characteristics with acceptable reliability and precision, both within (intratester) and between (intertester) testers. We also determined whether testers trained 18 months apart could perform these measurements with good agreement. Setting: University's Applied Neuromechanics Research Laboratory. Participants: Sixteen, healthy participants (7 men, 9 women). Assessment of Risk Factors: Six investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
145
5
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(174 citation statements)
references
References 33 publications
11
145
5
13
Order By: Relevance
“…The intrarater reliability of the navicular drop test was previously reported, with ICCs between 0.61 and 0.79, 68,73,86 whereas interrater reliability ranged from 0.46 to 0.83. 25,73,86,87 The validity agreement of the navicular drop test with values calculated from radiographs through radio-opaque markers affixed at the surface anatomical landmarks had good Pearson correlation coefficients (between 0.61 and 0.89). 37 As for relaxed calcaneal stance position, an earlier critical review of the literature concluded that this method was inherently unreliable and invalid.…”
Section: Discussionmentioning
confidence: 86%
“…The intrarater reliability of the navicular drop test was previously reported, with ICCs between 0.61 and 0.79, 68,73,86 whereas interrater reliability ranged from 0.46 to 0.83. 25,73,86,87 The validity agreement of the navicular drop test with values calculated from radiographs through radio-opaque markers affixed at the surface anatomical landmarks had good Pearson correlation coefficients (between 0.61 and 0.89). 37 As for relaxed calcaneal stance position, an earlier critical review of the literature concluded that this method was inherently unreliable and invalid.…”
Section: Discussionmentioning
confidence: 86%
“…This method recently has been reported to have an intraclass correlation coefficient (ICC) of 0.91 to 0.97 for intratester reliability. 21 Tibial Varum. This measure was performed with the participant in a weight-bearing, double-limb stance.…”
Section: Lower Extremity Alignment Data Collectionmentioning
confidence: 99%
“…This method of assessing Q angle has been reported to have an ICC of 0.89 to 0.98 for intratester reliability. 21 Genu Recurvatum. While standing, each participant was instructed to extend the knee as fully as possible.…”
Section: Lower Extremity Alignment Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations